X-men: apocalypse wars ebook - Hopeless, Dennis (X-Men: Apocalypse Wars., 2016)
Collects All-New X-Men (2015) #9-11, Extraordinary X-Men #8-12, Uncanny X-Men (2016) #6-10. As mutantkind's oldest enemy haunts the X-Men once again, three teams face war on multiple fronts, across different eras! The All-New X-Men are on a mission to write their own futures — especially Evan Sabahnur, destined to one day become Apocalypse! Trapped in Ancient Egypt, is he willing to escape his fate by changing the course of history? A thousand years from now, the Extraordinary X-Men are Homo superior's last hope against Apocalypse — but his newest Horseman is one of their own! And the Uncanny X-Men are drawn into the fray when Archangel once again assumes the guise of Death. Does this mean Apocalypse is rising again in the present — or will Magneto's team face a new kind of Genocide?